Methodological Review of Sampling Procedures for Rural Dwelling Sexual and Gender Minority People - Michael J Johnson; Tricia Gatlin (Rural Nurse Organization; Binghamton University, 2017)
Purpose: The purpose of this paper was to review the methodological sampling and recruitment decisions of extant studies that included rural dwelling sexual and gender minority populations.  Design and Sample: This review searched PubMed, CINAHL, and SCOPUS for papers using the following inclusion criteria: a) English language; b) primary quantitative research published in the last 10 years, and; c) included a rural adult sexual or gender minority sample from the United States. Exclusion criteria included: a) duplicate studies; b) datasets older than 10 years; c) secondary data, and; d) did not differentiate between rural and non-rural samples. Thirteen articles were included in the final review.    Results: This review identified the data collection approaches, rural classification systems, recruitment strategies, and sample demographics. Five areas were identified as needing further discussion, including the lack of dissimilar research topics, predominant focus on men, missed opportunity to identify transgender people, using social networks and smartphone applications as data collection strategies, and inconsistent rural classification systems. Conclusions: Researchers should capitalize on social networking and smartphone platforms. Future research should include sexual minority women, transgender people, more racial and ethnic minorities, and expand beyond sexual health topics. Researchers should also use objective rural classification systems. Keywords: Review; Homosexuality; Sexual Minorities; Transgender Persons; GLBT; Rural Population DOI:  http://dx.doi.org/10.14574/ojrnhc.v17i2.448